Effects of Glass Fibres on the Shear Strength of Soil - Chib, Vishal Singh (My University, 2016)
Soil reinforcement is not a new concept; it was used since ancient times to improve the shear strength/stiffness of soil. Fibre reinforced soil is termed as plysoil is a composite material obtained by mixing randomly distributed discrete fibres to soil (RDFS). The technique used for fibre inclusion in soil, is common, similar to soil stabilization. The main advantages of randomly distributed discrete fibres are the simplicity in mixing, maintaining the strength of reinforced soil over a long period of time. Reinforced soil can be advantageously used in civil engineering projects as a soil improvement technique with respect to; for providing sharp differences of level between two horizontal platforms, for providing horizontal platforms on sloping ground, as quay walls, as bridge abutments, subgrade/sub-base and in similar other slope stability problems. In present study glass fibre is used as a reinforced material to improve the shear strength of soil. Glass fibre is a non biodegradable material which provides durability to reinforced soil. The various physical properties of three different types of soils are found such as plastic limit, liquid limit, plasticity index, dry density, optimum moisture content etc. Inclusion of glass fibre at aspect ratio of 30, 45 and 60 to the soil with three different fibre content i.e. 0.5%, 1.0% and 1.5% was done. Then a series of direct shear test and triaxial test was conducted on both unreinforced and reinforced soil to study the behavior soil reinforced with glass fibre. After studying the results it clearly shows that the use of glass fibre with increase in aspect ratio and fibre content also increases the shear strength parameters of soil effectively.
Master of Engineering-Infrastructure Engineering
Keywords: Shear Strength; Glass Fibres; DST; CBR; TRIAXIAL